Land revenue, inequality, and development in colonial India (1880–1910) - Caum-Julio, Jordi (European review of economic history, 2024)
Abstract In my dissertation, I explore how colonial land institutions influenced both income inequality and the provision and funding of hospitals in colonial India. To do so, I present the first income inequality estimates assessing its evolution and levels across provinces and districts as well as a novel georeferenced hospital-level database. Findings suggest that the introduction of different colonial landownership rights—granting landownership and land revenue liability either to intermediaries or cultivators—explain differences in agricultural income inequality across districts and correlate with its evolution. These different landownership rights also affected the funding of hospitals through its interaction with local agency.